2017
DOI: 10.1039/c7cp02741a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local structure on photoluminescence properties of Eu3+ doped CeO2 red phosphors through induced oxygen vacancies by contrasting rare earth substitutions

Abstract: A new family of red phosphors, CeREO:0.1Eu (RE = Y and La; x = 0, 0.20, 0.40, 0.60, 0.80, and 0.90), was synthesized by a conventional solid-state route. The influence of contrasting rare earth substitutions (Y and La) in the system was investigated on the local structure and associated photoluminescence properties by various characterization techniques. Both trivalent ion substitutions lead to the same kind of variation during phase transformation from fluorite to the respective parent oxide structure (x ≥ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…Nakayama et al and Raj et al have showed the important role of the oxygen vacancies by the forming of the magnetization. We agree with this statement.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakayama et al and Raj et al have showed the important role of the oxygen vacancies by the forming of the magnetization. We agree with this statement.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Oxygen vacancies are the dominant defect species obtained by RE doping. They form associates with the RE ions, and the corresponding defect association energy is a strong function of the ionic radii of the RE dopants . In other words, Y 3+ dopant traps oxygen vacancies at the nearest‐neighbour site strongly, while La 3+ dopant repels oxygen vacancies at the nearest neighbor site.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The following reagents were used in the hydro and solvothermal synthesis of luminescent nanoparticles studied in this work: zirconium (IV) oxychloride octahydrate (98. 5…”
Section: Methodsmentioning
confidence: 99%
“…It is known that Ln 3+ -doped wide-bandgap semiconductor oxides can exhibit unique optical properties such as single or multicolor radiation, large Stokes shift, narrow spectral transition bands, long lifetime, and high photoluminescence quantum yield [2,3]. The optical properties of oxide nanoparticles doped with Ln 3+ largely depend on the type and structure of the host matrix [4,5]. Therefore, the correct selection of the absorption oscillator is significant for achieving the desired photoluminescence characteristics of lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%
“…O íon Eu 3+ é hipersensível ao ambiente químico no qual está inserido e, por esta razão, é utilizado como uma sonda espectroscópica, de forma que o perfil do espectro de emissão fotoluminescente observado fornece informações específicas sobre a estrutura da matriz hospedeira de acordo com a simetria dos sítios que o íon ocupa (CARNALL et al, 1989;KAUR et al, 2015;RAJ et al, 2017). Geralmente, as transições mais importantes para a determinação do sítio de ocupação dos íons Eu 3+ em uma estrutura cristalina são as transições 5 D0-7 F2 e 5 D0-7 F1, de maior intensidade.…”
Section: Espectroscopia De Fotoelétrons Excitados Por Raios X (Xps)unclassified